DNA damage and mitochondria-mediated apoptosis of A549 lung carcinoma cells induced by biosynthesised silver and platinum nanoparticles. Issue 33 (15th March 2016) - P. J., Shiny; Mukherjee, Amitava; Chandrasekaran, Natarajan
Abstract : Therapeutic potential of the biosynthesised silver and platinum nanoparticles against lung carcinoma cell line. Cellular death was induced by oxidative stress followed by apoptosis. Abstract : Silver and platinum nanoparticles were synthesised using the bioactive components from the macro alga Padina gymnospora. The efficiency of the nanoparticle as a suitable antitumor agent was tested against A549 lung carcinoma cells. The cell viability was assessed by MTT assay and the growth inhibition was observed. The synthesised silver and platinum nanoparticles arrested the cell growth in the G2 /M phase followed by a decline in cell number in the S phase. The cytotoxicity due to oxidative stress was investigated by measuring the enzymatic levels of stress markers such as GSH, LPO, catalase, and the subsequent LDH released, which was significant at elevated levels. The ROS generated by the nanoparticles and the consequential DNA damage was studied by the Hoechst staining and comet assay. The mechanism of cell death induced by the nanoparticles up-regulated the expression of apoptotic markers like p53, caspase 9, Bax, and simultaneously down-regulated the level of the antiapoptotic Bcl gene expression. These results suggest the activation of apoptosis and oxidative stress generated towards cell death in the cancer cells. Our investigations reveal that silver and platinum nanoparticles with further research can prove to be a potent targeted therapeutic agent with high efficacy against deadly tumours.